LITERATUR TAFSIR AL-QUR’AN DALAM BAHASA MELAYU-JAWI - Rahman, Arivaie (SUHUF, 2019)
The research on the heritage of the literature of Qur’anic interpretation in Indonesia has a lot been done. However, specific writing that studies on Qur’anic interpretation in Malay-Jawi scripts have not been done well yet. This article tries to make a period of history, to classify the typology, to reveal the author’s social background and to explain the characteristic of his Qur’anic interpretation. This article has made the periodization of of the Malay-Jawi Qur’anic interpretation into three periods: the first is the period of emergence (1600-1920), the second is the golden period (1920-1960), and the third is the period of decline (1960s). The typology of the Malay-Jawi Qur’anic interpretation can be classified into four catagories such as (1) the complete interpretation of the Qur’an, (2) interpretation of the certain suras in the Qur’an, (3) interpretation of the Qur’an based on the part of the Qur’an known as juz, and (4) thematic interpretation. The social background in the writing of the Malay-Jawi Qur’anic interpretation can be group into three main points such as (1) The background of the politics and governance, (2) the background of educational institution, and (3) the Islamic organization. As for the main character of the Malay-Jawi Qur’anic interpretation is sustained by the strength of language and script being used.